Unmasking Mutual Fund Derivative Use - Kaniel, Ron; Wang, Pingle (Review of Financial Studies, 2025)
Abstract Using new SEC data, we study fund derivative use and its impact on performance. Despite small portfolio weights, derivatives contribute largely to fund returns. Contrary to prior research, we find most employ derivatives to amplify, not hedge, equity returns. Using machine learning to classify funds’ derivative strategies reveals high specializations linked to information-related trading, liquidity management, gaining exposure, or hedging motives. Long index derivative users drive the amplification. During COVID-19, these users significantly increased derivative use more than others and shifted strategies, but initially lost on existing positions and then on newly opened short positions when markets unexpectedly rebounded.